Optimizing the Management of Facilities and Infrastructure to Improve the Quality of Student Learning - Prianto Anto; Ita Nurmalasari; Akhmad Shaiful Bakri (Al-Qalam Institue, 2026)
Quality education is vital for advancing societal progress, and the management of educational facilities and infrastructure plays a key role in enhancing learning outcomes. This study investigates the management and optimization of facilities at SMK Ma’arif NU 02 Kemiri Purworejo, focusing on its impact on student learning quality. The research aims to examine the processes of planning, utilization, maintenance, and optimization of educational facilities in a vocational setting. A qualitative approach was used, with data collected through structured interviews, direct observations, and document analysis. The findings reveal that while the school has made progress in managing its facilities, issues such as uneven facility utilization, limited funding, and reactive maintenance persist. The optimization efforts, including priority-based facility allocation and resource rotation, align well with educational needs. However, challenges in needs-based planning and equitable facility distribution require improvement. This research contributes to the academic literature by emphasizing the strategic role of facility management in vocational education, offering practical insights for improving learning environments. Future studies could explore broader institutional contexts and incorporate quantitative methods to strengthen the findings.